Socioeconomic status and preferences for income inequality: A quantitative study using the International Social Survey Program Data - Carreau,Aude Elisabeth Marguerite (2023)
People's preferences for income inequality vary, and this research investigates the influence of socioeconomic status on these preferences. Drawing on a structural position theory that considers individuals’ self-interest and rationality to be driven by their socioeconomic status, this paper examines the extent to which socioeconomic status affects the likelihood of accepting income inequality. Controlling for factors such as the perception of procedural justice, social mobility, and the level of income inequality, binary logistic regressions are conducted using a sub-sample of 15 European countries from the International Social Survey Program's 2019 "Social Inequality" module. The findings show that individuals with a high socioeconomic status are more likely to accept income inequality compared to those with a low socioeconomic status. Additionally, social mobility is shown to be an important factor in shaping people's acceptance of income inequality. Finally, perceiving a higher level of procedural justice significantly influences the acceptance of income inequality, albeit with a weak effect. These findings carry significant implications for society and politics, providing valuable insights into the dynamics of income inequality preferences; they can contribute to the development of policies aimed at promoting social and economic equity in the face of rising inequality.
Keywords: preferences; income inequality; socioeconomic status; meritocracy; social mobility